Pengaruh Jabatan, Budaya Organisasional dan Konflik Peran terhadap Hubungan Kepuasan Kerja dengan Komitmen Organisasi: Studi Empiris di Kantor Akuntan Publik - Dwi Cahyono; Imam Ghozali (The Indonesian Journal of Accounting Research, 2013)
Job  satisfaction  and organizational  commitment are two  things considered when discussing replacement of accounting firm employees. This  research examines causal  relationship between job  satisfaction  and organizational  commitment  through non-recursive model. Those  are organizational  post,  organization culture and  role  conflict as exogenous variables. The  data  of  this  research  collected through  mail  survey to overall accounting firm in several cities  in  Indonesia, those are: Ujung  Pandang, Denpasar, Surabaya, Malang, and  Semarang. The  Structural Equation  Modeling  is  used  for  developing   theoretical  model and  analyzing data.The  results  of  this  research show causal  relationship between  job  satisfaction and  organization  commitment.  Job  satisfaction  is negatively  related with organization  commitment, and  organization  commitment significantly and positively  influenced  to  job  satisfaction. Exogenous  variable for organization  post positively influences to organization  commitment  and positively  influences  job  satisfaction. Organization  culture in  accounting firm positively influences organization  commitment. Role  conflict significantly and negatively  influences to   job  satisfaction  and  positively and not significantly influences to  organization commitment.This research found that  organization  commitment in accounting firm come  first than job  satisfaction, and   organization culture in accounting firm  created by accounting firm management  strongly  influenced  organization  commitment and  later result in the  raise of  job  satisfaction of  accounting firm  employees. Role conflict  which occurred in accounting firm will negatively impact to job satisfaction and organization commitment. While,  the higher organization post the more influences  job satisfaction level and  organization commitment of accounting firm employees.